2015
DOI: 10.18298/ijlet.283
|View full text |Cite
|
Sign up to set email alerts
|

L1 Use in Individual Conferencing and Its effects on EFL Students' Writing Performances

Abstract: The present study investigates into the effects of L1 use in individual conferencing on EFL students' writing performances. Data were collected by analyzing students' first and second drafts of process and descriptive paragraph types. Two homogeneous groups of students whose language levels were determined with a proficiency exam at the beginning of the term participated in the study. One of the groups was randomly selected as an experimental group and the other as control group. The experimental group was ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In these studies, cognitive anxiety came first, followed by somatic anxiety, while avoidance behavior had the lowest mean. However, the dominant type of writing anxiety was different in a number of other studies (e.g., Alfiansyah et al, 2017;Ekmekçi, 2018;Min & Rahmat, 2014). These three studies revealed that somatic anxiety was the most common type of writing anxiety.…”
Section: Types Of Writing Anxietymentioning
confidence: 79%
“…In these studies, cognitive anxiety came first, followed by somatic anxiety, while avoidance behavior had the lowest mean. However, the dominant type of writing anxiety was different in a number of other studies (e.g., Alfiansyah et al, 2017;Ekmekçi, 2018;Min & Rahmat, 2014). These three studies revealed that somatic anxiety was the most common type of writing anxiety.…”
Section: Types Of Writing Anxietymentioning
confidence: 79%
“…In addition, recent studies (e.g. Blasco 2016;Ekmekçi 2018;Kara 2013;Khelalfa 2018;Kusumaningputri et al 2018;Rezaei and Jafari 2014;Jebreil, Azizifar and Gowhary 2015;Kırmızı 2015) accepted cognitive anxiety as the most powerful one compared to other two subtypes of anxiety namely somatic anxiety and avoidance behavior. On the other hand, somatic anxiety was associated with the perception of the individuals on the psychological impact of anxiety which can arise when negative feelings such as stress and apprehension were experienced.…”
Section: Affective Factors In Language Learningmentioning
confidence: 99%
“…He adds that translanguaging is a beneficial tool-aiding language teachers and accelerating students' language learning process, particularly for beginners first introduced to the TL's skillset. Ekmekçi (2015) indicates that EFL teachers use a bilingual approach to give instructions, develop strategies, and check comprehension. Pennycook (1994) calls monolingualism a "language [myth] of Europeans" (as cited in Ekmekçi, 2018:75).…”
Section: Introductionmentioning
confidence: 99%